Still see you everywhere - Gardner, Lisa. (New York : Grand Central, 2024)
"No man truly fears a woman. Not even one who is her father's daughter. The case was sensational. Kaylee Pierson had confessed from the very beginning, waived all appeals. She had called herself "death," but people called her the devil. Despite the media's chronicling of her tragic circumstances--the childhood spent with a violent father--no one could find sympathy for "the Beautiful Butcher" who had led eighteen men home from bars before viciously slitting their throats. Now, with only twenty-one days left to live, Pierson has finally received a lead on the whereabouts of the sister who was kidnapped over a decade ago, and she needs Frankie's help to find her. The Beautiful Butcher's offer: When was the last time your search ended with finding the living? Unable to resist the chance for a rescue, Frankie takes on Pierson's request. Twelve years ago, five-year old Leilani went missing in Hawaii. The main suspect? Pierson's tech mogul ex-boyfriend, Sanders MacManus. Now, on a remote island in the middle of the Pacific--the site of MacManus's latest vanity project--fresh evidence has appeared. In order to learn the truth and possibly save a young woman's life, Frankie must go undercover at the isolated base camp. Her challenge: A dozen strangers. Countless dangerous secrets. Zero means of calling for help. And then the storm rolls in ..."--
Keywords: Elkin, Frankie -- (Fictitious character) -- Fiction; Women private investigators -- Fiction; Cold cases (Criminal investigation) -- Fiction; Undercover operations -- Fiction; Secrecy -- Fiction; Serial murderers -- Fiction; Death row inmates -- Fiction; Siblings -- Fiction; Islands -- Hawaii -- Fiction; Trust -- Fiction; Storms -- Fiction; Private investigators -- Fiction; Women serial murderers -- Fiction; Missing persons -- Fiction; Large type books; Fiction; Large type books; Large print books; Detective and mystery fiction; Thrillers (Fiction)